Eyes/Open: Review of Jean-Christophe Bailly, The Animal Side - Csicsery-Ronay, Istvan (Humanimalia, 2014)
Jean-Christophe Bailly. The Animal Side. New York: Fordham UP, 2011. 87 pp. $65.00 hb, $18.00 pb.